Design Framework for a Modular Floating Container Terminal - Souravlias, Dimitris; Dafnomilis, Ioannis; Ley, Jens; Assbrock, Gerrit; Duinkerken, Mark B.; Negenborn, Rudy R.; Schott, Dingena L. (Frontiers in Marine Science, 2020)
The design and development of an offshore port terminal is a complex task that involves distinctive design and decision challenges. In this paper, we propose the implementation of a floating, modular, platform that can act as an additional terminal of a port, with the aim of expanding its current container handling capacity. To this end, we introduce a generic methodology to tackle three aspects of an offshore terminal: terminal layout design, strategic logistics optimization, and operational process coordination. The terminal layout design includes the modular arrangements, handling on and between platform modules by the associated equipment. To select the final layout design concept, we evaluate different alternatives on criteria such as layout complexity, scalability, and the number of moves associated with the modular nature of the platform. Subsequently, the selected concept is given as input to a strategic logistics optimization approach that introduces a mixed-integer linear programming model. The proposed model minimizes the capital, operational, and maintenance costs of the floating modular terminal, i.e., number and size of modules, number and type of equipment, as well as capacities. In parallel, we develop a simulation of the floating terminal’s hinterland connections, where the number and type of required vessels are specified for relevant destinations and transport configurations. At the operational level, we focus on the coordination of handling equipment on the offshore platform by employing a tailored simulation/optimization approach. Our methodology is demonstrated on a case study that considers accommodating the growth of a port in the Hamburg-Le Havre range via the use of a modular, floating, transport, and logistics hub.